2016
DOI: 10.1002/adfm.201601689
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Ionic Transport through Subnanometer Pores in Polymer Films

Abstract: Novel transport phenomena through nanopores are expected to emerge as their diameters approach subnanometer scales. However, it has been challenging to explore such a regime experimentally. Here, this study reports on polymer subnanometer pores exhibiting unique selective ionic transport. 12 μm long, parallel oriented polymer nanopores are fabricated in polyethylene terephthalate (PET) films by irradiation with GeV heavy ions and subsequent 3 h exposure to UV radiation. These nanopores show ionic transport sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
196
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 204 publications
(210 citation statements)
references
References 48 publications
9
196
1
4
Order By: Relevance
“…Indeed, the track consists of heavily damaged polymer, contains a high concentration of carboxylic groups and increased free volume due to amorphization and outgassing of volatile degradation fragments. At low pH, the carboxylic groups are protonated, which results in a decrease in the ionic permeability of the tracks . It is remarkable that the effect of the acidic stopping solution on the breakthrough time decreases with decreasing energy loss of the ion that produced the track.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the track consists of heavily damaged polymer, contains a high concentration of carboxylic groups and increased free volume due to amorphization and outgassing of volatile degradation fragments. At low pH, the carboxylic groups are protonated, which results in a decrease in the ionic permeability of the tracks . It is remarkable that the effect of the acidic stopping solution on the breakthrough time decreases with decreasing energy loss of the ion that produced the track.…”
Section: Resultsmentioning
confidence: 99%
“…The relative difference among the times of the through etching of Kr ion tracks caused by different pH values of the stopping solution is ≈30% on average (see Figure C). We assume this is ascribed to the fact that carboxylic groups play the role of a pH‐sensitive promoter of electrolyte diffusion through damage trails produced by energetic ions . As a consequence of lower dissipated energy the latent tracks of lighter ions contain fewer carboxylic groups, and the etchant penetration into the tracks is substantially slower and less influenced by pH.…”
Section: Resultsmentioning
confidence: 99%
“…Duan et al utilized ion‐track templates and electrochemical deposition to fabricate Cu nanocones and nanowire arrays . Wang and co‐workers fabricated nanoporous polymeric membranes using heavy ion irradiation and UV radiation . The typical fabrication process, MD simulations, and transport measurements are shown in Figure .…”
Section: Ion Beam Techniques For Materials Synthesis and Morphology Cmentioning
confidence: 99%
“…c) Ion conductance across the PET film as a function of ion fluence. Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: Ion Beam Techniques For Materials Synthesis and Morphology Cmentioning
confidence: 99%
“…With the help of electric and magnetic fields, the precise ion sieving has been achieved by controlling the interlayer distance of graphene oxide membranes. [27] Up to now, based on materials such as boron nitride, [28] CNTs, [29] polymers, [30] etc., researchers have prepared many kinds of highly selective separation membranes, which can mimic biological channels to realize water purification or ion sieving. [19] An experiment has shown that Aquaporins had a homotetramer structure with each subunit having an hourglass shape.…”
Section: Introductionmentioning
confidence: 99%